Bacteriological and ecfX- gene specific PCR based identification of Pseudomonas aeruginosa isolated from Chittagong industrial area and characterization of its extracellular amylase (Jahangirnagar University Journal of Biological Sciences, 2018)
Amylases are the starch degrading enzymes with applications ranging from food, fermentation, textiles to paper industries. In this study, a soil bacterium from the Chittagong industrial area was screened primarily for amylase activity using starch agar media. An attempt has been made to isolate and identify this amylolytic bacterium, optimization of its amylase production and characterization of the crude enzyme. The isolate was identified as Pseudomonas aeruginosa based on microscopic and biochemical tests. Beside this a speciesspecific gene ecfX (146 bp) for P. aeruginosa was amplified by PCR to confirm the identification of the isolate. A broad range of parameters for the optimization of enzyme production based on selection of best carbon and nitrogen sources, optimum pH, temperature, incubation period and effect of additional metal ions on culture media were investigated. Best enzyme activity (343.60 U/mL) was found in the presence of glucose as carbon source with yeast extract as nitrogen source at temperature 37°C after 24h at pH 9 in addition of Mg++ in submerged fermentation broth culture. The Mg++, SDS and Ca++ increased the amylase activity whereas EDTA and Zn++ were found as the inhibitory agents for amylase.Jahangirnagar University J. Biol. Sci. 7(2): 99-114, 2018 (December)